Distance Learning at University From A Lifelong Learning Perspective - Genute Gedviliene; Vilhelmina Vaiciuniene (European Scientific Journal, ESJ, 2016)
The paper discusses the importance of distance learning within university education. This issue stems from lifelong learning perspective, relating to social factors as emigration, demographic situation and competitiveness in the labour market. Distance learning is one of the possible solutions to acquire education to working people or those who live in remote locations. The main focus of our research was on learning quality and students’ satisfaction based on the case study of distance learning mode application. The research sample was composed of 126 part-time students who participated in the distance course organized as a part of university education. The case study of a distance course presented in this paper and survey findings revealed the study participants’ positive approach to distance learning in the university educational process. New technologies and their resulting opportunities for learners to interact with each other and with teachers, provision of guidance and logically structured material created preconditions for students’ satisfaction. Therefore, we assume that development of distance learning courses, constructivist learning environment with its inherent creative approach to learning provision can bring solutions to many social and educational issues, such as big emigration flows of young population, better employment opportunities and selfrealisation of young adults.